1999
DOI: 10.1007/s11746-999-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance liquid chromatography and spectroscopic studies on fish oil oxidation products extracted from frozen atlantic mackerel

Abstract: The formation of stable hydroxy derivatives from hydroperoxides produced during the oxidation of linoleic acid methyl ester and fish oil were studied by reverse-phase highperformance liquid chromatography (HPLC), gas chromatography-mass spectrometry (GC-MS) and 13 C nuclear magnetic resonance (NMR) spectroscopy. The oxidation products identified were mixtures of four isomeric hydroxy derivatives: 13-hydroxy-9-cis,11-trans-octadecadienoic,13-hydroxy-9-trans,11-trans-octadecadienoic, 9-hydroxy-10-trans,12-cis-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…The G ′ values obtained for the −10 °C stored fillets with vitamin E were closer to those of the −30 °C control fillets. The effect of the antioxidant on the rheological properties of frozen fillets suggests that lipid oxidation products produced from the polyunsaturated fatty acids during frozen storage2 interacted with the proteins either through a transfer of free radicals from the oxidised lipid to the proteins, as evidenced in our previous studies,3, 17 or via other protein–lipid interactions. The evidence for protein damage is supported by a number of model clinical studies;18–26 these show the formation of hydroperoxides on proteins and amino acids which were found to be reactive and to initiate and propagate the oxidation chain reaction themselves 19, 23, 26.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The G ′ values obtained for the −10 °C stored fillets with vitamin E were closer to those of the −30 °C control fillets. The effect of the antioxidant on the rheological properties of frozen fillets suggests that lipid oxidation products produced from the polyunsaturated fatty acids during frozen storage2 interacted with the proteins either through a transfer of free radicals from the oxidised lipid to the proteins, as evidenced in our previous studies,3, 17 or via other protein–lipid interactions. The evidence for protein damage is supported by a number of model clinical studies;18–26 these show the formation of hydroperoxides on proteins and amino acids which were found to be reactive and to initiate and propagate the oxidation chain reaction themselves 19, 23, 26.…”
Section: Resultsmentioning
confidence: 73%
“…In our laboratory we have studied the biochemical changes that occur in fatty fish during frozen storage. These studies indicated denaturation of the myofibrillar proteins1 as well as lipid oxidation of the polyunsaturated fatty acids docosahexaenoic and eicosapentaenoic acids, which may be minimised with the aid of antioxidants 2. We also showed the transfer of free radicals from oxidised fish oil to myosin by electron spin resonance spectroscopy, followed by myosin aggregation as indicated by fluorescence spectroscopy 3.…”
Section: Introductionmentioning
confidence: 65%
“…29 The minced mackerel (from whole fillets) was homogenised with methanol/chloroform (2:1 v/v) for 4 min. The fish homogenate was centrifuged for 10 min at 3000 × g. The lower chloroform phase containing the lipid was filtered and chloroform was evaporated off.…”
Section: Lipid Extractionmentioning
confidence: 99%
“…Mackerel has a high content of PUFAs (24.8%), including linoleic, linolenic, eicosapentaenoic acid 20:5 (n-3) (EPA) and docosahexaenoic acid 22:6 (n-3) (DHA), 29 which provide abundant substrate for forming 4-HNE. Lipid hydroperoxides formed at -80°C at -10°C (250 mg kg −1 green tea) at -10°C (500 mg kg −1 green tea) at -10°C enzymatically and non-enzymatically decompose to various adducts incorporating aldehydes such as 4-HNE.…”
Section: Mechanism and Significance Of 4-hne Formation In Stored Mackmentioning
confidence: 99%
“…As previously reported by our laboratory (39), these signals are in the spectral region that is characteristic of conjugated diene lipid oxidation products (LOPs), and careful consideration of their chemical shift values, and the coupling pattern of that at 6.38 ppm, indicates that they are attributable to one or more conjugated hydroxydiene species [e.g., 13-hydroxy-9-cis,11-trans-octadecadienoate derived from the peroxidation of the low levels of 18:2(n-6) present], the determination of which is known to be of practical value in the monitoring of fish and fish oil quality (40). Experiments to determine the nature and content of such LOPs in cod liver oil supplements are currently in progress in our laboratory, the results of which will be presented elsewhere.…”
Section: D 1 H Nmr and 2d 1 H-1 H Nmr Analysis Of Minor (Low-level) mentioning
confidence: 99%